PERUBAHAN KARAKTERISTIK PEMBENTUKAN POLIURETAN BERBASIS HTPB DAN TDI BERDASARKAN KOMPOSISI REAKSI (CHANGES IN THE FORMATION CHARACTERISTICS OF POLYURETHANE BASED ON HTPB AND TDI REACTION COMPOSITION) - Rosita , Geni (Indonesian Journal of Aerospace, 2016)
Polyurethane formation occurs through crosslinking of a reaction between the hydroxyl group (OH) of HTPB and isocyanate (NCO) of TDI. Polymer network formation reaction will be formed from the linear bond and a combination of crosslinking. At longer reaction, the polyurethane chains are formed increasingly long and followed by changes in the characteristics. If the reaction has been perfect then the polyurethane chain isÂ straight and it will become more flexible. Â This research aimed to obtain polyurethane as fuel binder, which was indispendable in solid composite propellant manufacturing. Several samples of existing HTPB were made into a different composition of HTPB/TDI. The process used Â reaction kinetics methods based on the composition in order to obtain the mechanical properties of polyurethane. Â Average molecular weight, crosslinking density, hardness, and swelling were analized to determine the quality of polyurethane as fuel-binder. The analysis was a consideration for determining the most suitable fuel-binder composition. It was also to test the quality of experimental HTPB produced by LAPAN HTPB Laboratory (HTPBlocal) as an initial procedure in the propellant manufacturing. The analysis showed different results for each composition. The compositions that could be used as the fuel-binder for the formation of polyurethanes were: HTPBA at 7: 1; HTPBB at 9: 1; HTPBC at 8: 1; and HTPBD at 8: 1; whereas HTPBE could not be used because required advanced processing.